Women and Consistorial Discipline: The Case of Courthézon in the Early Seventeenth Century. Issue 2 (June 2019) - Meyer, Judith P.
Abstract : This study seeks to contribute to a more nuanced understanding of both the Reformed church consistory and women's experience of the Reformation by examining the interactions between the Reformed church consistory and women in the small French town of Courthézon. For the period from 1617 to 1631, it analyzes how the consistory treated women in its exercise of discipline and how women in turn treated the consistory. It examines in-depth a number of cases of women summoned by the consistory for various offenses, including quarreling, dancing, marital and sexual relations, and absence from services. The interactions were complex and suggest that both male patriarchy and female agency were at work. Yet the consistory also treated the two sexes similarly in certain instances. Women demonstrated a remarkable capacity to ignore, negotiate with, and on occasion defy the consistory. One extraordinary woman rejected the consistory's authority altogether when pressed to reconcile. The cases also indicate that the process of consistorial discipline aided women by providing opportunities for them to represent and act for themselves. The consistory was guided by a desire to keep its minority community intact: it showed remarkable patience, forbearance, and a willingness to compromise in its efforts, and it consequently was usually successful.